PRIVILEGES OF THE SPECIAL REGION OF YOGYAKARTA (DIY) IN THE CONTEXT OF LOCAL GOVERNMENT LAW POLITICS - Milenia Ramadhani (Jurnal Impresi Indonesia, 2025)
The Special Region of Yogyakarta (DIY) has a privileged status based on historical, philosophical, juridical, and socio-psychological aspects that distinguish it from other regions in Indonesia. The legal politics of local governments in Indonesia adheres to an asymmetrical decentralization system that allows for differences in authority for certain regions, including DIY. This study aims to analyze the privileges of DIY in the context of local government legal politics, focusing on the legal basis, implementation, and impact on local government governance. The method used is a juridical-normative approach with descriptive analysis, where data is obtained through a literature study of relevant laws and regulations, such as Law Number 13 of 2012 concerning DIY Privileges, as well as related academic literature. The results of the study show that Yogyakarta has five special authorities, namely in filling the positions of Governor and Deputy Governor, local government institutions, culture, land, and spatial planning. In addition, this privilege is also followed by the provision of special funds to support the implementation of the policy. In conclusion, the uniqueness of DIY is a form of recognition of the history and culture inherent in the region as well as the implementation of asymmetric decentralization in the local government system in Indonesia. This research provides a deeper understanding of how legal politics supports the sustainability of the privileged status of DIY within the framework of the Unitary State of the Republic of Indonesia.